Analysing Shari’ah Compliant Retirement Planning: the Case of Malaysia - Hussain, Hafezali Iqbal; Shamsudin, Mohd Farid; Alaeddin, Omar; Hadi, Abdul Razak Abdul; Saleh, Nor Effuandy Pfordten Md; Sabli, Norhaila; Jabarullah, Noor H (International Journal of Engineering and Technology, 2018)
This paper analyses the retirement planning scenario in Malaysia with an emphasis on the Private Retirement Scheme which gives tax deductions of RM 6,000.00 per year for individual taxation. The need for retirement is dire in the country given that more than half of the population have savings of less than RM 50,000.00 in their Employee Provident Fund by the time they are 50. The analysis shows that PRS penetration is low and is only beneficial for those in the top tax bracket. In addition, the returns given by the funds have been insufficient to attract sufficient participation amongst Malaysians.